Health‐Related Quality of Life Following Total Laryngectomy: A Systematic Review. (31st August 2020) - Wulff, Nille B.; Højager, Anna; Wessel, Irene; Dalton, Susanne O.; Homøe, Preben
Abstract : Objective: Treatment of advanced laryngeal and hypopharyngeal cancer has shifted from total laryngectomy (TL) toward laryngeal‐preserving therapies due to a general perception that TL has a significantly negative impact on the individual's life. However, whether the physical impairments related to TL translate to a reduced health‐related quality of life (HRQoL) has not yet been determined. Therefore, the objective of this systematic review was to determine how HRQoL is affected following TL. Methods: Systematic searches were conducted in PubMed, Embase, and Cochrane. Inclusion criteria were original studies describing quality of life following TL after larynx/hypopharynx cancer using a formally developed patient‐reported questionnaire. Study quality assessment was carried out with the tool developed by the National Heart, Lung, and Blood Institute. Results: Forty‐six studies using 12 different questionnaires were included. The majority were cross‐sectional (85%), and study quality was rated poor in 30%, fair in 30%, and good in 39% of studies. When comparing results from the four most frequently used questionnaires with normative data, we found that in more than 60% of studies, differences to the reference population were of clinical importance, with only few exceptions. Conclusions: In general, we found that people who received TL have a worse HRQoL than the male normative reference population. However, even though TL patients experience a clinically important difference in many domains when compared with normative data, their burden of symptoms is generally mild. The current review also makes it evident that despite the relatively large number of studies conducted, the strength of evidence remains weak. Laryngoscope, 131:820–831, 2021